Vegetative propagation in Celtis australis : Effect of season and auxin treatment - MEHTA, HARSH; KAUSHAL, RAJESH; RAJKUMAR, RAJKUMAR; GUPTA, ANAND KUMAR; THAPLIYAL, SHANKAR DAYAL (The Indian Journal of Agricultural Sciences, 2021)
Celtis australis is one of important multipurpose tree species of north western Himalayas. The natural regeneration of the tree is very poor owing to huge biotic pressure. The tree therefore needs to be propagated by vegetative means. An experiment was conducted to ascertain the effect of season and IBA concentrations on rooting behaviour of Celtis australis. Cuttings collected in three different seasons, viz. spring, summer and rainy were subjected to different lndole- 3-Butyric Acid (IBA) treatments, viz. 250, 500, 750, 1000ppm and control. Maximum rooting (30.6%) was observed in rainy season. Rooting was higher (49.4%) in 250 ppm IBA concentration. Interaction effect of season × treatment revealed that maximum rooting (59.3%) was recorded during rainy season when cuttings were treated with 250 ppm IBA. The results of the study are useful for mass multiplication and cloning the species for enhancing productivity.